Protozoa in the digestive tract of wild herbivores in South Africa. I: Warthogs (Phacochoerus aethiopicus) - Booyse, Dirk G.; Boomker, Elizabeth A.; Dehority, Burk A. (Zootaxa, 2010)
Seventeen warthogs were harvested from their natural habitat during the winter hunting seasons of May to July 2001 and May to June 2002. Samples (200ml each) were collected and weighed from the stomach, cecum and colon of each animal for protozoal counts. Telamodinium onyx was the only protozoa present in seven animals and the predominant species in all others. Megadinium aethiopicum was observed in eight animals, while Teratodinium sphaeredon was present in two warthogs. Several different species of protozoa were seen in a few animals, two of which belong to the family Ophryoscolecidae and are considered to be normal inhabitants in the rumen (Diplodinium dentatum and Ophryoscolex purkynjei).